Correlations between cystic fibrosis genotype and sinus disease severity in chronic rhinosinusitis. (29th November 2017) - Abuzeid, Waleed M.; Song, Changeun; Fastenberg, Judd H.; Fang, Christina H.; Ayoub, Noel; Jerschow, Elina; Mohabir, Paul K.; Hwang, Peter H.
Abstract : Objective: Cystic fibrosis (CF) patients commonly develop chronic rhinosinusitis (CRS). The impact of the most common cystic fibrosis transmembrane conductance regulator (CFTR) mutation, F508del, on the severity of sinonasal disease remains inconclusive. The objective of this study is to evaluate the impact of CFTR genotype functional classification on sinonasal disease severity in patients with CRS. Methods: Retrospective chart review of patients with CF who underwent endoscopic sinus surgery for chronic rhinosinusitis from 1998 to 2015. Patients were divided into high‐ or low‐risk genotypes based on standardized CFTR gene functional classification. The primary outcome was the 22‐item Sino‐Nasal Outcome Test (SNOT‐22) score. Secondary outcomes included endoscopic scores, extent of surgery performed, presence of polyposis, number of revision surgeries, and Lund‐MacKay computed tomography scores. Results: Thirty‐eight patients harbored a high‐risk CFTR genotype, and 11 had a low‐risk genotype. On bivariate analysis, there was no association between CFTR genotype risk stratification and measures of preoperative disease severity or postoperative outcomes. There were no associations between genotype risk stratification and outcome variables on multivariate linear regression, adjusted for age and gender. There were significant improvements in several SNOT‐22 subdomains before and after endoscopic sinus surgery ( P < 0.05), but the magnitude of improvement was not significantly different on the basis of CFTR genotype risk stratification. Conclusion: High‐risk CFTR genotypes are not associated with worse sinonasal disease severity or postoperative symptom control than low‐risk CFTR genotypes after adjusting for confounding factors. Level of Evidence: Level 4. Laryngoscope, 1752–1758, 2018